PENINGKATAN KETERAMPILAN DIGITAL GURU MELALUI PELATIHAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS WORDWALL - Annisa; Sarifa; Saugadi Saugadi (Makapande Mengabdi: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
The development of information technology has brought significant changes to the field of education, including teaching methods and learning media. Teachers are required to possess adequate digital skills to create interactive learning experiences that are relevant to the needs of the 21st century. However, many teachers in rural areas still lack the ability to optimally utilize interactive learning media. This community service activity aimed to improve teachers’ digital skills through training on the use of Wordwall as an interactive learning medium. The activity was conducted at SDN 3 Malala, Dondo Subdistrict, Tolitoli Regency, involving eight participants consisting of classroom teachers and subject teachers. The implementation methods included interactive lectures, demonstrations, hands-on practice, mentoring, and evaluation. The results showed an increase in teachers’ knowledge and skills in creating and implementing Wordwall-based learning media. Teachers found the media easy to use, flexible, and effective in enhancing students’ learning motivation and participation. This program is expected to serve as a model for digital skills training for teachers in other schools, especially in areas with limited access to technology training.